Efficiency of soil and fertilizer phosphorus use : - Syers, J.K (Food and Agriculture Organization of the United Nations, 2008)
This report has benefited from the valuable inputs provided at all stages of its preparation by the other joint sponsors: the fercilizer Institute, the International Fertilizer Industry Association, the International Plant Nutrition Institute, and the World Phosphate Institute.